(untitled) (Fiep Bulletin - online, 2013)
According to ativo.com, we live in a country where the Cult of the body is becoming very important in people’s lives. And according still with ativo.com, following this, the number of gymnastics academies has grown very much and Minas Gerais has become the second largest brazilian state in this sector. Nowadays, there are here 8200 gymnastics academies, 2800 clubs, stadiums and sporting centers. We can say that according to this number, the rendering of services is quickly developing itself. And how are the gymnastics academies in BH evaluating if their clients are satisfied or not with the quality of services rendered? This is a question that has to be answered as quickly as possible, so that we can have clients who are totally satisfied with the services rendered and to make us able to continuously improve the quality of our work. Due to that, a research was done in the gymnastics academies with the objective of evaluate some mechanisms that are used to measure client satisfaction and the rendering of services. 20 medium sized gymnastics academies were researched (300 to 2000 students – PEREIRA, 1996. Apud MARINHO, Luciana Cristina Figueiredo, ARAÚJO, Marcilene Canabrava, s.d.) from Savassi’s PU (Planning Unity) region, composed of Santo Agostinho, Lourdes and Funcionários quarters, being 11 the number of those who answered the questionnaire, meaning that 91% make use of some type of tool to evaluate client satisfaction.